BIINER LEARNING MODEL TO IMPROVE STUDENT’S SCIENTIFIC ATTITUDE - Rahmatul Husna Arsyah; Ambiyar; Faeza Rezi; Rizky Ema Wulansari (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
This study aims to assess the effectiveness of the BIINER Learning model in shaping students' scientific attitudes. This study uses a type of quasi-experimental experiment. Data was collected through questionnaires and observations. Data on students' scientific attitudes between the BIINER Learning group and the Project based learning group were analyzed using the T test. The results of the data analysis show that the value of tcount (5.772) is greater than ttable (2.381), which means that there is a significant difference in scientific attitude between the BIINER Learning group and the Project based learning group. Thus, it can be concluded that the BIINER Learning model is more effective in cultivating students' scientific attitudes than the Project based Learning model. Observational data also supports this conclusion. The scientific attitude of students in the BIINER Learning group showed a percentage of 8.3% (moderate), 47.2% (high), and 44.4% (very high), while the Project based learning group showed a percentage of 22.2% (moderate), 50% (high), and 27.7% (very high). Thus, students' scientific attitudes in the BIINER Learning model tend to be higher than Project based learning in the very high category, while in the medium and high categories, the percentage of students' scientific attitudes in the Project based learning model is higher than BIINER Learning. In conclusion, the use of the BIINER Learning model is more recommended because it is proven to be more effective in shaping students' scientific attitudes. Thus, it can be expected that students' scientific attitudes can develop better through the application of this learning model